Knitting topological bands in artificial sonic semimetals. (January 2021) - Zheng, Li-Yang; Zhang, Xiu-Juan; Lu, Ming-Hui; Chen, Yan-Feng; Christensen, Johan
Abstract: Frontier investigations on a contemporary family of materials comprise a new class of topological materials that have been discovered in three dimensional (3D) semimetallic crystals. Beyond already unconventional topological quasiparticles in Dirac and Weyl semimetals, nodal-line semimetals provide an even richer platform encompassing robust band-touching manifolds and exotic transport properties. Classical configurations including artificial crystals have emerged as popular systems not only to replicate these new properties in wave-based scenarios, but particularly also to ease experimental complexities of electronic systems and to permit topological tuning via variable geometrical designs. Sonic crystals are one of such example, in which dissimilar fluid or rigid inclusions or channels are combined to tailor the acoustic material response at will. Here, we design a cubic lattice of guiding channels allowing us to map topological characteristics of quasi-particles excitations to audible sound properties. Simply by varying the cross section of these channels, we bring forward multiple phase transitions among four different interlaced nodal features, which resemble the knitting of 3D Bloch-bulk bands in momentum space. One nodal attribute appears to feature an acoustic version of directional massless Dirac fermions, which is experimentally characterized and displays linear crossing in one direction and flat bands in the perpendicular one, enabling strongly focused and collimated sound beams, thanks to this peculiar dispersion. Highlights: An acoustic 3D cubic structure is constructed to emulate sound waves with exotic semimetallic properties. Highly complex band degeneracies with multiple interlaced nodal features are for the first time experimentally detected. A directional Dirac cone is observed which permits the collimation and focusing of sound. Furthermore, we explore quasi-flat topological surface states.